83.1k views
2 votes
Simplify (x+2y)(x-2y)​

User Jan Berndt
by
4.4k points

2 Answers

0 votes
X^2-4y^2 would be your answer
User BenCr
by
5.5k points
4 votes

Answer:

x² - 4y²

Explanation:

Step 1

On expansion,

(x + 2y)(x - 2y) = x(x - 2y) + 2y( x - 2y)

= x(x) - x(2y) + 2y(x) + 2y(-2y)

= x² - 2xy + 2xy - 4y²

= x²- 4y²

Each of the terms are perfect squares

x² = x X x

4y² = (2y)² = 2y X 2y

Hence, x² - 4y² is the difference of two squares.

Simplification of (x+2y)(x-2y) gives x²-4y² which is the difference of two squares

User Kiddouk
by
5.1k points